Digital light 3D printing of double thermoplastics with customizable mechanical properties and versatile reprocessability - Zhu, Guangda; Coelln, Nadine von; Hou, Yi; Vázquez-Martel, Clara; Spiegel, Christoph A.; Tegeder, Petra; Blasco, Eva (Advanced materials, 2024)
Digital light processing (DLP) is a 3D printing technology offering high resolution and speed. Printable materials are commonly based on multifunctional monomers, resulting in the formation of thermosets that usually cannot be reprocessed or recycled. Some efforts are made in DLP 3D printing of thermoplastic materials. However, these materials exhibit limited and poor mechanical properties. Here, a new strategy is presented for DLP 3D printing of thermoplastics based on a sequential construction of two linear polymers with contrasting (stiff and flexible) mechanical properties. The inks consist of two vinyl monomers, which lead to the stiff linear polymer, and α-lipoic acid, which forms the flexible linear polymer via thermal ring-opening polymerization in a second step. By varying the ratio of stiff and flexible linear polymers, the mechanical properties can be tuned with Young's modulus ranging from 1.1 GPa to 0.7 MPa, while the strain at break increased from 4% to 574%. Furthermore, these printed thermoplastics allow for a variety of reprocessability pathways including self-healing, solvent casting, reprinting, and closed-loop recycling of the flexible polymer, contributing to the development of a sustainable materials economy. Last, the potential of the new material in applications ranging from soft robotics to electronics is demonstrated.